2020
DOI: 10.1002/chem.202003039
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of CO2 at Coinage Metal Nanodendrites in Aqueous Ethanolamine

Abstract: Electrocatalytic reduction of CO 2 into usable chemicals is ap romising path to addressc limate changea nd energy challenges. Herein, we demonstrate the synthesis of unique coinagem etal (Cu, Ag, and Au) nanodendrites (NDs) via af acile galvanic replacement reaction(GRR), which can be effective electrocatalysts for the reductiono fC O 2 in an ethanolamine(EA) solution. Each metal ND surface was directly grown on glassy-carbon(GC) substrates from am ixture of Zn dust and the respective precursors olution. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…As discussed later, this study evidences the significance of supporting electrolyte selection when amines are used to deliver CO 2 to the electrode. Additional studies have further examined amine-CO 2 reduction in aqueous electrolytes using Cu, Ag, and Au ( Hossain et al., 2021 ), and reported up to 58% FE to CO at ∼20 mA/cm 2 on Cu ( Abdinejad et al., 2020 ), an atypically high FE for this catalyst.…”
Section: Exemplar Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed later, this study evidences the significance of supporting electrolyte selection when amines are used to deliver CO 2 to the electrode. Additional studies have further examined amine-CO 2 reduction in aqueous electrolytes using Cu, Ag, and Au ( Hossain et al., 2021 ), and reported up to 58% FE to CO at ∼20 mA/cm 2 on Cu ( Abdinejad et al., 2020 ), an atypically high FE for this catalyst.…”
Section: Exemplar Processesmentioning
confidence: 99%
“…Electrochemically reactive capture has so far been found capable of yielding a range of products depending on the electrolyte medium, such as carbon monoxide (CO) ( Chen et al., 2017 ; Abdinejad et al., 2020 ; Hossain et al., 2021 ; Lee et al., 2021 ; Pérez-Gallent et al., 2021 ), formate (HCOO − ) ( Chen et al., 2017 ; Bhattacharya et al., 2020b ; Pérez-Gallent et al., 2021 ), and solid alkali carbonates ( Khurram et al., 2018 ), often with high selectivity. Although prior studies have now demonstrated basic scientific feasibility, given the early stage of the field, influential parameters and rate-limiting factors have not yet been thoroughly studied, and rational design of such processes is not yet possible.…”
Section: Introductionmentioning
confidence: 99%
“…The advanced hybrid structures were used for the detection of melamine in milk and thiram in apple juice at trace level concentrations. The same methodology (electrodeposition) was adopted by another group of Rafatmah to synthesize AuNDs on paper substrates for nonenzymatic determination of glucose. An alternative approach by Calamak demonstrated the well-controlled multibranched AuNDs by adopting a dynamic microfluidic flow scheme …”
Section: Metal Nanodendrites Decorated On Si Substratementioning
confidence: 99%
“…A few studies reported that applying porous electrodes can improve product Faradaic efficiency. For example, Chen et al 60 Reproduced with permission 74 , copyright 2020, John Wiley and Sons.…”
Section: Electrode Materials and Structuresmentioning
confidence: 99%
“…Therefore, the porous microstructure could be beneficial for CO 2 conversion. In another example, Hossain et al 74 prepared nano dendrites based on Cu, gold (Au), and Ag by growing the metals on a glassy carbon via a galvanic replacement reaction in the mixed solution of metal precursors and Zn dust. (see Fig.…”
Section: Electrode Materials and Structuresmentioning
confidence: 99%